A prospective randomised non-blinded comparison of conventional and Dorgan's crossed pins for paediatric supracondylar humeral fractures. Issue 11 (November 2016) - Dučić, Sinisa; Radlović, Vladimir; Bukva, Bojan; Radojičić, Zoran; Vrgoč, Goran; Brkić, Iva; Jaramaz Dučić, Tatjana; Jurdana, Hari; Abramović, Dusan; Bojović, Nikola; Štefan, Lovro
Abstract: Background: Closed reduction and percutaneous pinning are the preferred treatment of displaced supracondylar humeral fractures in children. The purpose of this study is to evaluate the non-standard Dorgan's method and compare its results with those of the standard percutaneous cross pinning method in treatment of unstable or irreducible Gartland type II and III supracondylar humeral fractures in children. Patients and methods: This was a prospective evaluation of 138 consecutive patients with Gartland type II or III extension supracondylar humeral fractures referred to University Children's Hospital during a four-year period. The patients were randomized into two groups: the first group, comprised of 71 patients, was treated with standard pin configuration and the second group, comprised of 67 patients, underwent Dorgan's method. The study included 88 boys and 50 girls aged 1.5–11.4 years (mean 6.5 ± 2). At initial presentation 8.7% (n-12) fractures were classified as Gartland type IIa, 25.4% (n-35) as Gartland type IIb and 65.9% (n-91) as Gartland type III. Results: Flynn's criteria were used to evaluate the results. An excellent clinical outcome was reported in about 90% of patients (n-90) treated with standard pin configuration and 89.5% (n-60) of patients treated with Dorgan's method. There were no statistically significant differences in outcomes between the groups in terms of their gender, age, fracture types, function and cosmetics. Neurological lesions were observed in 9.9% of patients (n = 7) who were treated using the standard configuration Kirschner pins, while in those treated by Dorgan's method neurological complications were not observed. However, the procedure time was longer (mean 36.54 ± 5.65 min) and radiation exposure significantly higher (mean 10.19 ± 2.70 exposures) in the group that was treated using Dorgan's method, compared to the conventional method (mean 28.66 ± 3.76 min and 7.54 ± 1.63 exposures). Conclusion: Two laterally inserted crossed pins provide adequate stability with good functional and cosmetic outcome for most unstable paediatric supracondylar humeral fractures with no risk of iatrogenic ulnar nerve injury.